2015
DOI: 10.1016/j.fuproc.2014.11.021
|View full text |Cite
|
Sign up to set email alerts
|

Emission of carbon monoxide, total hydrocarbons and particulate matter during wood combustion in a stove operating under distinct conditions

Abstract: Wood combustion experiments were carried out to determine the effect of ignition technique, biomass load and cleavage, as well as secondary air supply, on carbon monoxide (CO), total hydrocarbon (THC), particulate matter (PM 10 ) and particle number emissions from a woodstove. Wood from two typical tree species in the Iberian Peninsula was selected: pine (Pinus pinaster) and beech (Fagus sylvatica). The highest CO and total hydrocarbon emission factors (EFs) were observed, respectively, for pine and beech, for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
32
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(36 citation statements)
references
References 43 publications
(70 reference statements)
4
32
0
Order By: Relevance
“…Samples were analysed for organic and elemental carbon (OC/EC), levoglucosan and 56 elements. The information provided in the present study complements that given by Vicente et al (2015), in which combustion temperatures, burn rates, emissions factors (g kg −1 of wood burned, dry basis) of both PM 10 and flue gases, as well as particle number size distributions, were explored.…”
Section: Introductionmentioning
confidence: 83%
See 1 more Smart Citation
“…Samples were analysed for organic and elemental carbon (OC/EC), levoglucosan and 56 elements. The information provided in the present study complements that given by Vicente et al (2015), in which combustion temperatures, burn rates, emissions factors (g kg −1 of wood burned, dry basis) of both PM 10 and flue gases, as well as particle number size distributions, were explored.…”
Section: Introductionmentioning
confidence: 83%
“…The lower density of softwood promotes higher combustion rates compared to those observed for hardwood. Softwood burns quickly and, thus, the occurrence of oxygen deficit zones in the combustion chamber is likely to occur (Vicente et al, 2015). The PM 10 from the top-down ignition using beech wood consisted of OC and EC in almost equal fractions, which indicates combustion under higher temperatures.…”
Section: Particulate Carbonaceous Contentmentioning
confidence: 99%
“…Further, an improvement in combustion quality can be achieved with catalytic support to the post-combustion process, even in the phases of lower combustion temperatures (Butschbach et al, 2009). It was reported that operational conditions, like the ignition technique (upside-down or bottom-up), fuel type and use of split or non-split firewood, also have a strong influence on the combustion quality (Vicente et al, 2015).…”
Section: B Ojha Et Al: High-temperature Co / Hc Gas Sensorsmentioning
confidence: 99%
“…After the reloading of firewood on the glue bed (t Re ∼ 67 min and 52 min for the hand-and automatically controlled stoves, respectively), the firing process is completely different compared to the previous process. This is because now the burning proceeds from the bottom of the wood (Vicente et al, 2015). With controlled airstreams well adapted to this new firing situation, the Tc can be maintained rather high (about 400 • C) and stable for a longer time, and the CO concentration is typically reduced to values below 700 ppm for more than 20 min (Fig.…”
Section: Validation Of Control Conceptmentioning
confidence: 99%
“…Vincente et al [6] describe wood combustion experiments. The goal of study was to determine the effect of ignition technique, fuel load and cleavage as well as secondary air supply on carbon monoxide, total hydrocarbon, particulate matter (PM10) and particle number emissions from a wood stove.…”
Section: Introductionmentioning
confidence: 99%